Medication use patterns in the visually impaired in Saudi Arabia and the importance of applying Braille labeling - May Almukainzi; Arwa Almuhareb; Fatima Aldwisan; Wasaal Alquaydhib (Elsevier, 2020)
Background: A visually impaired person typically faces countless challenges throughout their daily activities. These challenges can include medication safety and efficacy. Few studies have addressed the issues of safety and pattern of medication usage in visually impaired patients, or the need to apply Braille labeling to medications dispensed to these patients. Objective: To explore the medication use pattern in severely visually impaired and blind patients living in Saudi Arabia, and to evaluate the need for Braille labeling on medication dispensed to these patients. Method: The merits of the proposal and its alignment with national regulations were evaluated and the study was approved by the Institutional Review Board (IRB). This cross-sectional study was conducted through open- and closed-ended questionnaires that were distributed to 215 visually impaired people, aged 18 years and above, dispersed throughout different cities within the kingdom. Result: The sample population was equally distributed in terms of sex. The majority of the participants were young with a college degree. More than half of the participants were unable to identify the name, dose, expiry date, instructions and interactions of their medication, and the respondents usually relied on their caregivers. 91% of the respondents agreed that application of Braille labeling on their medications would improve the quality of their therapy and help them overcome some of their difficulties. Conclusion: This study investigated medication usage patterns in the visually impaired in Saudi Arabia. These patients face considerable challenges to any efforts to self-administer their own medication and are heavily reliant on caregivers. The current methods for dispensing medications to this population, (and current regulations) do not sufficiently meet their health information needs. The study highlighted the necessity of applying Braille labeling to medicines prescribed to the visually impaired. A reconsideration of the current regulations regarding the application of Braille labeling to medications is warranted. The use of Braille labeling on medications may improve drug treatment regimes, minimize medications errors, and promote independence in these individuals (through self-administration of medications). The addition of technology to the printed Braille labeling can advance the pharmaceutical care services provided and improve the life quality of patients. Keywords: Visually impaired, Saudi Arabia, Pharmaceutical services, Braille labeling, SFDA, Blinds, Drug QR code